2022
DOI: 10.1002/cnma.202200283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oriented Assemblies of SrTiO3 with Exposed (200) Plane on Photocatalytic Hydrogen Evolution

Abstract: This study aims to investigate the effect of crystallographic orientation of the assemblies of SrTiO3 (formed on a glass substrate) on photocatalytic hydrogen evolution. For this, we have successfully synthesized nanocubes of SrTiO3 through a hydrothermal method. Assemblies on the glass substrate were formed by using functionalized/non‐functionalized oxide over functionalized/non‐functionalized glass substrate. The functionalization of the oxides and the glass substrate was carried out using IPTMS (3‐iodopropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Many reports in the literature support this fact. In one of our studies, 24 we have also shown that oxygen vacancies present in oriented assemblies of SrTiO 3 had a significant role in the HER. The presence of defect structures is a result of various factors.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Many reports in the literature support this fact. In one of our studies, 24 we have also shown that oxygen vacancies present in oriented assemblies of SrTiO 3 had a significant role in the HER. The presence of defect structures is a result of various factors.…”
Section: Resultssupporting
confidence: 62%
“…The peak centered at ∼531 eV corresponds to the presence of defects that are created due to oxygen vacancies in the oxide. 24–28 Thus, analysis of the oxides using XPS confirmed the presence of defects arising due to oxygen vacancies. This observation led us to analyze further the oxides for the nature of the vacancies and their concentration.…”
Section: Resultsmentioning
confidence: 88%
“…The XRD pattern of STO/Rh (3%) was totally consistent with the standard pattern of cubic perovskite-structured STO (JCPDS no. 00-035-0734, space group: Pm 3 m ) . X-ray photoelectron spectroscopy (XPS) was performed for STO/Rh (3%) surface analysis.…”
Section: Resultsmentioning
confidence: 99%
“…00-035-0734, space group: Pm3m). 28 X-ray photoelectron spectroscopy (XPS) was performed for STO/Rh (3%) surface analysis. The peaks of the Rh 3d, Ti 2p, Sr 3d, and O 1s were observed at 309.74, 458.14, 113.62, and 529.95 eV, respectively.…”
Section: Characterizations Of Sto/rh (3%) and Othermentioning
confidence: 99%